Implementation Of The Special Education Programme (Learning Disabilities) In Penang: An Evaluation From Special Education Teachers’ And Programme Coordinators’ Perspectives - Lee , Seoh Choon (2011)

(untitled)
This study evaluates the special education programme for students with learning disabilities in Penang in three main domains: (a) school administrative policy in planning and implementation, teachers’ training and support, and resources available for teaching/learning, (b) special education delivery system in planning and collaboration for teaching, instructional strategies and learning activities, application of teaching/learning resources, student evaluation system/process and classroom management, and (c) program outcome in term of students’ participation, progress/improvement and achievement.